ANALISIS PELAKSANAAN PROGRAM KEAGAMAAN DALAM UPAYA MEMBINA KEPRIBADIAN ISLAMI SISWA SMP NEGERI 2 GUNUNG TOAR KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Novianti Novianti; Andrizal Andrizal; A Mualif (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
The research is motivated by the importance of implementing religious programs in schools for students of SMP Negeri 2 Gunung Toar. Currently, many institutions, both Madrasah and General Schools, have implemented various activities in the Religious Program as an effort to foster the Islamic personality of students, so that PAI educators or teachers are required to be able to keep up with the times so that religious activities that are applied do not lag behind, this development one of which includes how to manage the class with appropriate learning methods so that learning objectives can be achieved optimally. SMP Negeri 2 Gunung Toar is one of the institutions that makes religious program one of the autonomous subjects included in the curriculum. Not only in general learning, other religious program activities must also have the right learning method so that students can follow the learning process well and later the Islamic personality of students can increase. Based on the background and phenomena above, this study aims to analyze whether the Religious Program at SMP Negeri 2 Gunung Toar can foster Islamic personality for students at SMP Negeri 2 Gunung Toar. This research is a qualitative research with descriptive type. Data cpllection techbiques used are observation, interviews and documentation. Data analysis uses data collection, data reduction, presenting data, making conclusions. The results of the study indicate that the religious program in an effort to foster the Islamic personality of the students of SMP Negeri 2 Gunung Toar can be said to be quite good.